A survey of cybersecurity for intelligent connected-automated vehicle - Yufeng LI; Xiaoyuan LU; Chenhong CAO; Jiangtao LI; Hongyi ZHU; Nan MENG (Dianxin kexue)
The automotive industry is experiencing a shift to an intelligent and connected paradigm.(Semi-) Autonomous vehicles use a new generation of information and communication technologies to realize a full range of interactions between vehicles and cloud,vehicles and vehicles,vehicles and roads,and vehicles and pedestrian,etc.When cars started to become connected computers on wheels,network security became a major challenge,and because the scope of cyber threats extended from virtual space to physical space,the harm of cybersecurity had risen to human life.The electronic/electrical structure,in-vehicle network structure,and out-of-vehicle network structure of intelligent vehicles were introduced,the security requirements of vehicle networks were elaborated,several cyber-attacks against connected-automated vehicle (CAV) were pointed out,the available defense measures against these attacks were addressed.The advantages and disadvantages of these measures were summarized.Finally,possible defense measures and directions in the future were discussed to further ensure the security of CAV.